2013
DOI: 10.1007/978-3-642-41335-3_10
|View full text |Cite
|
Sign up to set email alerts
|

One License to Compose Them All

Abstract: In the domain of Linked Open Data a need is emerging for developing automated frameworks able to generate the licensing terms associated to data coming from heterogeneous distributed sources. This paper proposes and evaluates a deontic logic semantics which allows us to define the deontic components of the licenses, i.e., permissions, obligations, and prohibitions, and generate a composite license compliant with the licensing items of the composed different licenses. Some heuristics are proposed to support the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 22 publications
(47 reference statements)
0
21
0
Order By: Relevance
“…The MK:Smart project has collected a large quantity of data sources about the city of Milton Keynes [8]. The datasets used in the study 9 In particular, they were suggested to answer the following questions: what is the nature of the input data? What is the purpose of the process?…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The MK:Smart project has collected a large quantity of data sources about the city of Milton Keynes [8]. The datasets used in the study 9 In particular, they were suggested to answer the following questions: what is the nature of the input data? What is the purpose of the process?…”
Section: Methodsmentioning
confidence: 99%
“…Data consumers might need to check which original sources of the data need to be acknowledged because of an attribution requirement, and even whether the form of exposure or re-distribution they employ is allowed according to the policies attached to each individual piece of data they might obtain from the Data Hub. Research on policy models and reasoning focuses on the problem of licence compatibility and composition [2,9]. However, reasoning on policy propagation is a necessary preliminary step to any policy validation or consistency check.…”
Section: Context and Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…43 In 2013, the G8 started the Open Data Charter, 44 also includes legal information as a pillar for enhancing law. For this reason the Open Government Data movement is no longer limited to government organizations but extends its reach to other public bodies, especially to parliamentary bodies (e.g., the Italian Parliament 45 and the US House of Representatives, 46 the Open Government Partnership, 47 and the National Library of Congress of Chile 48 ), and the judiciary (the Open Justice Project in the UK, 49 US Open Data Justice, 50 the California Initiative, 51 the European Court of Justice 52 ). Moreover, thanks to the PSI Directive, the emphasis is also placed on public documents, and not only on public data, enriched with RDF metadata.…”
Section: Semantic Web and Public Administration: The Open Government mentioning
confidence: 99%
“…But all three initiatives are market, governance, and policy regulators, and on top of them SW languages can be used to generate the automated selection and aggregation of relevant information to perform legal acts. Information from disparate and heterogeneous sources often produces incompatible or contradictory results, and these kinds of problems need to be tackled in advance [51]. For instance, Natural Language Processing and the representation of norms in RuleML can be used to perform business contracts; Ontology Design Patterns (ODP) make it pos-58 https://www.w3.org/community/pua/wiki/Digital_Rights_ Management.…”
Section: The Web Of Data and The Law: A Step Forwardmentioning
confidence: 99%